Ceramic sintering aid and application thereof

By combining manganese dioxide and modified aluminum powder in the ceramic sintering aid, the elemental solution of manganese ions and the chemical stability of the alumina coating are used to form a high-density and corrosion-resistant ceramic material, which solves the contradiction between ceramic density and acid corrosion resistance, and achieves the efficient sintering and corrosion resistance of ceramics.

CN119569467AActive Publication Date: 2025-03-07CENT SOUTH UNIV +1

Patent Information

Application Number
CN202411752892.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

While the existing ceramic sintering additives improve the density and sintering properties of ceramics, they will reduce the acid corrosion resistance of ceramics, and the process is complicated, making it difficult to implement industrially.

Method used

Using a ceramic sintering aid including 2-4 parts of manganese dioxide and 4-8 modified aluminum powder, a high-density corrosion-resistant ceramic material is formed through the elemental solution of manganese ions and the chemical stability of the alumina coating layer, combined with the low melting point of aluminum particles and the coating effect of epoxy resin.

Benefits of technology

The high density and corrosion resistance of ceramics are achieved, the production cost of ceramics is reduced, the process flow is simplified, and the feasibility of industrial implementation is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005165441350000053
    Figure BDA0005165441350000053
  • Figure BDA0005165441350000071
    Figure BDA0005165441350000071
  • Figure BDA0005165441350000081
    Figure BDA0005165441350000081
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic membranes, in particular to a ceramic sintering aid and application thereof. The ceramic sintering aid is prepared from, by weight, 2-4 parts of manganese dioxide and 4-8 parts of modified aluminum powder, the modified aluminum powder comprises aluminum particles, and the surfaces of the aluminum particles are wrapped with epoxy resin layers. The mass ratio of the aluminum particles to the epoxy resin is (2-3): 1. Based on the fact that low-valence manganese ions are not resistant to corrosion, the corrosion resistance of the manganese ion-containing ceramic is improved by wrapping the ceramic particles with the corrosion-resistant layer. Meanwhile, the melting point of aluminum oxide is extremely high, and a coating layer is very difficult to form, so that aluminum powder is coated with resin, ceramic is sintered in an inert gas atmosphere, the resin is gasified at a high temperature, and aluminum is molten to form a liquid phase to coat raw material particles; after cooling, the atmosphere is changed into an air atmosphere, so that the molten aluminum is oxidized to form a compact aluminum oxide layer, low-valence manganese oxide which is easily corroded by acid is isolated, and the high-compactness and corrosion-resistant performance of the ceramic is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic membranes, and in particular to a ceramic sintering aid and application thereof. Background Art

[0002] The performance of honeycomb ceramic thermal storage body is an important indicator of RTO. The dense ceramic can provide better mechanical properties and can accommodate more heat per unit volume, which can effectively improve the life of the ceramic.

[0003] Prior art CN 107445627 B relates to a method for preparing a double-layer coated ceramic powder of phenolic resin and manganese dioxide, comprising the following steps: (1) adding potassium permanganate to deionized water to prepare a homogeneous solution, and evenly distributing the ceramic powder in the homogeneous solution; (2) dripping manganese acetate solution into the mixed solution, filtering, drying and sieving to obtain MnO2-coated ceramic powder; (3) mixing the MnO2-coated ceramic powder and phenolic resin, adding a sufficient amount of ethanol solvent, and rotary evaporating to a small amount of ethanol; (4) taking out the composite powder, drying, grinding and sieving to obtain a double-layer coated ceramic powder of phenolic resin and manganese dioxide. The invention has a simple process, good coating effect and low equipment requirements, effectively solves the problems of uneven distribution of sintering aids in the matrix and uneven distribution of binders in the ceramic powder, and can effectively improve the sintering performance and mechanical properties of ceramic parts. However, its sintering aid manganese dioxide will reduce the acid corrosion resistance of the ceramic. At the same time, the co-precipitation method for preparing coating materials is complex and difficult to achieve industrially.

[0004] Prior art CN 118459232 A discloses an alumina ceramic membrane sintering aid and a preparation method and application thereof, relating to the field of ceramic membrane technology. The alumina ceramic membrane sintering aid is composed of nano silicon oxide and foaming powder, and the foaming powder includes 20 parts of alumina powder, 5080 parts of potassium feldspar, 520 parts of sodium feldspar, 0.11 parts of sodium carboxymethyl cellulose, 0.11 parts of sodium tripolyphosphate, 0.53 parts of sodium hexametaphosphate, 0.31 parts of 1000 mesh manganese dioxide, 0.10.6 parts of 1000 mesh silicon carbide, and 100 parts of water. The particle size of the alumina ceramic membrane sintering aid of the invention is controllable, and the temperature can be controlled when it is used in the preparation process of the alumina ceramic membrane support. In the preparation process of the alumina ceramic membrane support, the nano-silicon dioxide in the sintering aid can adjust the viscosity of the high-temperature liquid, and accelerate the reaction between the sintering aid and the alumina powder, which has a greater bridging effect. The porous liquid at high temperature can ensure the strength of the alumina ceramic membrane support and increase the porosity. However, its manganese dioxide will reduce the acid corrosion resistance of the ceramic, and the alumina sintering is difficult. Summary of the invention

[0005] The object of the present invention is to provide a ceramic sintering aid for improving the density and corrosion resistance of ceramics and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A ceramic sintering aid comprises, by weight, 2-4 parts of manganese dioxide and 4-8 parts of modified aluminum powder, wherein the modified aluminum powder comprises aluminum particles, the surfaces of which are coated with an epoxy resin layer; the mass ratio of the aluminum particles to the epoxy resin is 2-3:1.

[0008] The present invention promotes ceramic densification through the elemental solid solution of manganese ions, and at the same time utilizes the chemical stability of the aluminum oxide coating layer to isolate the corrosion source. However, since the melting point of aluminum oxide is relatively high and the coating process is complicated, the present invention uses aluminum particles as the aluminum source to introduce aluminum oxide. The melting point of metallic aluminum is low, and the high-temperature aluminum liquid has good fluidity and can spread on the surface of the particles to form an aluminum liquid coating layer of the ceramic raw material during the sintering process. After cooling, the sample is exposed to the air to oxidize the aluminum to form an aluminum oxide coating layer. Since aluminum is relatively active, aluminum oxidation must be avoided before sintering, otherwise aluminum liquid will not be formed during the sintering process. Therefore, the present invention utilizes epoxy resin to coat aluminum powder to effectively isolate the air, thereby avoiding aluminum oxidation during the ceramic preparation process, ensuring that aluminum liquid can be formed to wrap the ceramic during the sintering process, and at the same time promoting the densification of the ceramic. The oxidized aluminum oxide layer plays a role in isolating the corrosion source.

[0009] In a preferred embodiment, the preparation method of the modified aluminum powder comprises the following steps: uniformly dispersing aluminum particles and epoxy resin in a solvent, and obtaining the modified aluminum powder after drying.

[0010] In a preferred embodiment, the added mass of the solvent is 4-9 times the mass of the solid.

[0011] With anhydrous ethanol (ethyl acetate) as solvent, aluminum particles and epoxy resin are dispersed into a 10wt%-20wt% solution, stirred for 30-60 minutes under a magnetic stirrer to prepare a dispersion, and then the dispersion is placed in a vacuum drying oven and solidified to obtain modified aluminum powder.

[0012] In a preferred embodiment, the drying time is 3-5 hours and the temperature is 50-70°C.

[0013] If the curing time is too short, it will lead to incomplete curing and poor surface quality; if the curing time is too long, it will lead to hardness and brittleness of the surface coating.

[0014] In a preferred embodiment, the solvent is ethanol or ethyl acetate.

[0015] In a preferred embodiment, the solvent is anhydrous ethanol or ethyl acetate.

[0016] Water has poor solubility for epoxy resin and will react with aluminum particles, resulting in a serious decline in ceramic performance; solvents with a high evaporation rate, such as acetone, will cause uneven coating during the curing process. Anhydrous ethanol and ethyl acetate have good solubility for epoxy resin and a moderate evaporation rate, which can make the coating layer evenly distributed.

[0017] In a preferred embodiment, the epoxy resin is bisphenol A epoxy resin.

[0018] In a preferred embodiment, the viscosity of the epoxy resin is 100-500 mPa·s.

[0019] If the viscosity is too high, it will be difficult to mix evenly with aluminum powder; if the viscosity is too low, it will be difficult to effectively adhere to the surface of aluminum powder.

[0020] In a preferred embodiment, the epoxy equivalent of the epoxy resin is 150-200 g / eq.

[0021] In a preferred embodiment, the particle size D50 of the modified aluminum powder is 5-10 μm, and the particle size distribution (D90D10) / D50≤3.0.

[0022] Based on the same inventive concept, the present invention provides the use of the ceramic sintering aid in the preparation of a honeycomb ceramic thermal storage body.

[0023] Based on the same inventive concept, the present invention provides a honeycomb ceramic heat storage body, including the ceramic sintering aid.

[0024] In one preferred embodiment, the honeycomb ceramic thermal storage body also includes: 40-60 parts of bauxite powder, 2-7 parts of cordierite powder, 1-4 parts of Suzhou kaolin, 0.5-1.5 parts of pyrope powder, 20-35 parts of mullite powder, 2-5 parts of potassium feldspar, 3-9 parts of raw talc; 0.2-0.5 parts of dispersant, and 0.5-0.2 parts of grinding aid.

[0025] In a preferred embodiment, the dispersant is sodium acrylate.

[0026] In a preferred embodiment, the grinding aid is glycerol.

[0027] In a preferred embodiment, the aluminum oxide content in the bauxite powder is >80%.

[0028] Based on the same inventive concept, the present invention provides a method for preparing the honeycomb ceramic thermal storage body, comprising the following steps:

[0029] The raw materials except the ceramic sintering aid are mixed and ball-milled to obtain a mixed material;

[0030] The mixed material, the kneading agent and the ceramic sintering aid are mixed, kneaded, refined, molded and dried to obtain a dry blank;

[0031] The dry blank is sintered to obtain the honeycomb ceramic heat storage body.

[0032] In a preferred embodiment, the kneading agent includes 1-4 parts of cellulose, 1-3 parts of palm oil, and 0.3-1 part of polyethylene oxide.

[0033] In a preferred embodiment, the viscosity of the cellulose is 80,000-120,000; the melting point of palm oil is 24-28°; and the molecular weight of polyethylene oxide is 1-8 million.

[0034] In a preferred embodiment, the sintering process is: in a nitrogen atmosphere, the temperature is increased to 850-950°C at a rate of 5-10°C / min, and then the temperature is increased to 1200-1300°C at a rate of 2-4°C / min, and the temperature is kept for 2-3h; then the temperature is cooled, and the nitrogen atmosphere is maintained during the cooling process. When the temperature drops below 300°C, the nitrogen is stopped and the temperature is continued to cool to room temperature.

[0035] Kneading, refining, compression molding and drying are all common steps and means for preparing honeycomb ceramic thermal storage bodies.

[0036] The beneficial effects of the present invention are:

[0037] The present invention has developed a sintering aid for a highly dense and corrosion-resistant ceramic material. The manganese dioxide and aluminum particles used are low in price, and the density of the ceramic sample sintered in a nitrogen atmosphere is extremely high. The increase in density comes from the elemental solid solution of the added manganese dioxide and the low-valent manganese ions decomposed at high temperature with the ceramic matrix. The lattice distortion caused by the solid solution greatly increases the diffusion rate of the material, and the high-temperature liquid phase formed by the melting of aluminum powder in a nitrogen atmosphere can also promote mass transfer and fill pores, thereby obtaining a highly dense ceramic. However, low-valent manganese ions are not corrosion-resistant. The present invention improves the corrosion resistance of manganese-ion-containing ceramics by wrapping ceramic particles with a corrosion-resistant layer. Alumina has good chemical stability, but its melting point is extremely high, and it is very difficult to form a coating layer. Therefore, the present invention coats aluminum powder with resin to avoid oxidation of the aluminum powder during the treatment process before sintering; the modified aluminum powder is sintered in an inert gas atmosphere, the resin is vaporized at high temperature, and the aluminum melts to form a liquid phase with good fluidity to wrap the raw material particles; after cooling, it is changed to an air atmosphere, so that the aluminum liquid is oxidized to form a dense aluminum oxide layer, isolating the low-valent manganese oxide that is easily corroded by acid, so as to achieve the high density and corrosion resistance of the prepared ceramic. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a flow chart for preparing the high-density, corrosion-resistant honeycomb ceramic according to Example 2 of the present invention. DETAILED DESCRIPTION

[0039] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict. Unless otherwise specified, the relevant percentages refer to mass percentages.

[0040] Example 1

[0041] Effect of Manganese Dioxide Addition on Ceramics Properties

[0042] The high-density honeycomb ceramic heat storage body includes basic raw material powder and other components. The basic raw material powder is composed of the following basic raw materials by weight (kg): 55 parts of bauxite powder with an aluminum oxide content of> 80%, 5 parts of cordierite powder, 2 parts of Suzhou kaolin, 0.5 parts of pyrope powder, 30 parts of mullite powder, 3.5 parts of potassium feldspar, and 4 parts of raw talc. Then, sodium acrylate, a dispersant, is added at 5‰ of the total mass of the basic raw material powder, glycerin, a grinding aid, is added at 2‰ of the total mass of the basic raw material powder, and then manganese dioxide is added at 0%, 2%, 4%, 6%, 8%, and 10% of the total mass of the basic raw material, respectively, and the sample performance is tested.

[0043] The preparation method of the high-density honeycomb ceramic thermal storage body is as follows:

[0044] Weigh each raw material by weight, put the raw material into a ball mill, and ball-mill for 6 hours at a speed of 30 revolutions per minute to obtain a mixture; add the mixture into a kneader, add 2% of 100,000 viscosity cellulose by weight of the mixture, 2% of 28-degree palm oil, 8‰ of 5 million molecular weight polyethylene oxide, and 13% of deionized water, set the kneader speed to 30 revolutions per minute, knead for 20 minutes, and obtain a kneaded mud segment; put the kneaded mud segment into a vacuum mud kneading machine, and refine it at a vacuum degree of 0.07 to obtain a refined mud segment; use a mold to press it into the desired product to obtain a wet blank; dry the wet blank to obtain a dry blank; cut both ends of the dry blank, and the cutting size is 1.20 times the length of the finished product to obtain a cut dry blank; put the cut dry blank into a kiln, heat it to 900°C at a rate of 5°C / min, and then heat it to 1250°C at a rate of 3°C / min, and keep it warm for two hours.

[0045] Measure the true density, sintering line shrinkage, water absorption and thermal expansion coefficient of the sample. The specific test method is as follows:

[0046] The true density test method is implemented in accordance with the national standard GB / T 24203-2024.

[0047] The thermal expansion coefficient test method is implemented in accordance with the national standard GB / T 16920-2015.

[0048] The calculation method of sintering line shrinkage is:

[0049] Wherein, L% is the sintering line shrinkage; L1 is the length of the sample before sintering; L2 is the length of the sample after sintering.

[0050] The water absorption rate is calculated as follows:

[0051] Among them, M% is the water absorption rate; M1 is the mass before water absorption; M2 is the mass after water absorption.

[0052] The sample was then immersed in a 28% sodium hydroxide solution and magnetically stirred at 25° C. for 96 hours, and the mass loss rate of the sample was measured.

[0053] The sample was immersed in a 50% dilute sulfuric acid solution and magnetically stirred at 25°C for 96 hours. After drying, the mass loss rate of the sample was measured to characterize the acid and alkali corrosion resistance of the sample.

[0054] The test results are shown in Table 1.

[0055] Table 1 Effect of different contents of manganese dioxide on ceramic properties

[0056]

[0057] It can be seen from Table 1 that with the increase of manganese dioxide addition, the true density of the sample gradually increases. When the addition amount reaches 4wt%, the true density of the sample reaches the maximum, and when the addition amount is 6wt%, the true density of the ceramic decreases rapidly.

[0058] From the perspective of sintering line shrinkage and water absorption, with the increase of manganese dioxide addition, the shrinkage of ceramic sintering line shows an upward trend, and the water absorption shows a downward trend. When the manganese dioxide addition is 6wt%, the ceramic volume further shrinks on the basis of 4wt%, but the true density is much smaller than when the addition is 4wt%. The possible reason for this volume shrinkage and true density reduction is that, on the one hand, the change in the amount of manganese dioxide added will cause the ceramic phase and content to change accordingly, and on the other hand, manganese dioxide will decompose into low-valent manganese oxides and oxygen at high temperatures. The released oxygen causes the mass to decrease, so even if the volume shrinks, its true density still decreases.

[0059] From the weight loss rate after acid-base treatment, with the increase of manganese dioxide, the alkali resistance of the ceramic is enhanced, reaching the highest at 4wt%, and then the alkali resistance decreases due to the increase of glass phase content in the ceramic; with the increase of manganese dioxide, the acid resistance of the ceramic gradually weakens. Manganese dioxide itself is insoluble in cold sulfuric acid. The weakening of acid resistance is due to the increase of glass phase on the one hand, and on the other hand, manganese dioxide decomposes into low-valent manganese oxides at high temperature. Low-valent manganese oxides are soluble in most inorganic acids. Therefore, the weight loss rate of the ceramic in dilute sulfuric acid solution gradually increases.

[0060] From the perspective of thermal expansion coefficient, the increase in thermal expansion coefficient of ceramics with the addition of 2wt% and 4wt% manganese dioxide is small, indicating that manganese dioxide promotes the production of less liquid phase. When the manganese dioxide addition amount is 6wt%, the thermal expansion coefficient of ceramics increases significantly. This is because excessive addition of manganese dioxide leads to a large amount of liquid phase generated.

[0061] When the amount of manganese dioxide added exceeds 6%, the ceramic sample shows "bubbling" phenomenon, which sharply deteriorates the surface morphology of the ceramic. Therefore, the amount of manganese dioxide added should not be too much. When the amount added is 4%, the sample has a high density and the thermal expansion coefficient is improved by a small margin. However, the acid resistance of the sample with added manganese dioxide deteriorates because low-valent manganese ions easily react with acids. In order to improve the corrosion resistance of manganese-containing ceramics, the present invention considers adding aluminum powder in the form of composite to form an alumina coating in situ, and using the excellent chemical stability of alumina to improve the problem of decreased acid resistance caused by manganese ions.

[0062] Example 2

[0063] Effect of 4% manganese dioxide + different contents of aluminum powder on ceramic properties

[0064] according to Figure 1 The process shown is for preparing a high-density, corrosion-resistant ceramic material, including a basic raw material powder and other components. The basic raw material powder is composed of the following raw materials in parts by weight (kg): 55 parts of bauxite powder with an aluminum oxide content >80%, 5 parts of cordierite powder, 2 parts of Suzhou kaolin, 0.5 parts of pyrope powder, 30 parts of mullite powder, 3.5 parts of potassium feldspar, 4 parts of raw talc, 5‰ of the total mass of the basic raw material powder as a dispersant sodium acrylate, 2‰ of the total mass of the basic raw material powder as a grinding aid glycerin, and 4wt% of the total mass of the basic raw material powder as manganese dioxide.

[0065] Weigh each raw material by weight, put the raw material into a ball mill, and ball-mill for 6 hours at a speed of 30 revolutions per minute to obtain a mixture; disperse aluminum particles in anhydrous ethanol to prepare a dispersion with a solid content of 40-60wt%, and simultaneously dissolve an epoxy resin accounting for one third of the mass of the aluminum particles in the anhydrous ethanol, wherein the epoxy resin is a bisphenol A type epoxy resin with a viscosity of 400mPa·s and an epoxy equivalent of 150g / eq; stir for 30 minutes under a magnetic stirrer; and place the dispersion in a vacuum drying oven and dry at a temperature of 60°C for 4 hours to obtain modified aluminum powder coated with organic matter. Add the mixture to a kneader, add 2% of 100,000 viscosity cellulose, 2% of 28 degree palm oil, 8‰ of 5 million molecular weight polyethylene oxide, 13% of deionized water and the above-mentioned certain amount of modified aluminum powder, set the kneader speed to 30 revolutions per minute, knead for 20 minutes, and obtain a kneaded mud segment; put the kneaded mud segment into a vacuum mud kneading machine, and refine it at a vacuum degree of 0.07 to obtain a refined mud segment; use a mold to press it into the desired product to obtain a wet blank; put the wet blank into a vacuum drying oven and dry it at 125°C for 4 hours to obtain a dry blank; put the dry blank into a kiln, and heat it to 900°C at a rate of 5°C / min under a nitrogen atmosphere, and then heat it to 1250°C at a rate of 3°C / min, and keep it warm for two hours. During the cooling process, keep the nitrogen atmosphere with the furnace cooling, stop the nitrogen when the temperature drops to about 300°C, and expose the sample to the air to obtain the sample.

[0066] Measure the true density, sintering line shrinkage, water absorption and thermal expansion coefficient of the sample. The specific test method is the same as above.

[0067] The sample was immersed in 28% sodium hydroxide solution and magnetically stirred at 25°C for 96 hours, and the mass loss rate of the sample was measured;

[0068] The sample was immersed in a 50% dilute sulfuric acid solution and magnetically stirred at 25°C for 96 hours. After drying, the mass loss rate of the sample was measured to characterize the acid and alkali corrosion resistance of the sample.

[0069] The test results are shown in Table 2.

[0070] Table 2 Effect of 4% manganese dioxide + modified aluminum powder with different contents on ceramic properties

[0071]

[0072] When 2, 4, 6, 8, and 10% of modified aluminum powder are added to the manganese dioxide at a dosage of 4%, the density of the ceramic increases first and then decreases. This is because the modified aluminum powder in the nitrogen atmosphere forms a liquid phase at high temperature to promote mass transfer and fill pores; when the ceramic sample is cooled to about 300°C after sintering and exposed to the air, the oxidation of aluminum brings a certain volume expansion. When the expansion degree is within a certain range, the ceramic matrix presents a compressive stress state, which can play a role in ceramic toughening. However, with the increase of the amount of modified aluminum powder added, excessive expansion leads to a deterioration of the density of the ceramic. With the increase of the amount of modified aluminum powder added, the acid and alkali corrosion resistance of the ceramic increases first and then decreases. The improvement of corrosion resistance shows that the strategy of forming a liquid phase at high temperature and exposing it to oxidation in the air after cooling can play the role of isolating corrosive substances, but with the increase of the amount of modified aluminum powder added, the density of the ceramic weakens. When the amount of added is greater than 6%, the weight loss rate of the sample in the acid and alkali solution increases. Therefore, the appropriate amount of modified aluminum powder added is 4-8%.

[0073] Example 3

[0074] Effect of epoxy resin addition on ceramic properties,

[0075] The difference between this embodiment and embodiment 2 is that the addition amount of modified aluminum powder is fixed at 6%, and the proportion of epoxy resin is changed. The properties of the prepared ceramic samples are shown in Table 3.

[0076] Table 3 Effects of different ratios of modified aluminum powder and epoxy resin on ceramic properties

[0077]

[0078] When the ratio of aluminum particles to epoxy resin is 2-3:1 (especially 3:1, that is, the mass proportion of epoxy resin is 1 / 4-1 / 3), the density and corrosion resistance of the ceramic reach a peak. The possible reason is that too little epoxy resin cannot cover the aluminum powder, resulting in oxidation of part of the aluminum powder and poor sintering density of the ceramic; too much epoxy resin will cause excessive gas produced after the decomposition of organic matter, acting as a pore-forming agent. The pores inside the ceramic sample increase the contact area between the sample and the corrosion source. The same amount of aluminum powder added has limited isolation effect, which also leads to a decrease in corrosion resistance.

[0079] Example 4

[0080] The influence of different solvents on the ceramic properties. The difference between this embodiment and embodiment 2 is that the addition amount of the modified aluminum powder is fixed to 6%, and the addition amount of the epoxy resin is one third of the mass of the aluminum powder, and the influence of different solvents on the ceramic properties is investigated. The properties of the ceramic samples prepared using different solvents are shown in Table 4.

[0081] Table 4 Effect of different solvents on ceramic properties

[0082]

[0083]

[0084] Due to the different solubility of different solvents for epoxy resin and the different volatility of the solvents, the effects of different solvents on the quality of the organic coating layer are very significant. Pure water has poor solubility for epoxy resin and will react with aluminum powder, resulting in oxidation of the aluminum powder, and basically cannot provide effective performance improvement for the ceramics; the evaporation rate of acetone is relatively high, which may cause cracking of the organic coating layer during the ceramic drying process; anhydrous ethanol and ethyl acetate have better solubility for epoxy resin, and their volatilization rates are moderate, which can effectively control the drying and curing rate. In the present invention, the solvent should be anhydrous ethanol or ethyl acetate.

[0085] Example 5

[0086] Effects of different organic coating materials on ceramic properties

[0087] The difference between this embodiment and embodiment 2 is that the addition amount of modified aluminum powder is 6% of the base powder, and phenolic resin is used to replace epoxy resin. The effects of different coating materials on ceramic properties are shown in Table 5.

[0088] Table 5 Effects of different organic coating materials on ceramic properties

[0089]

[0090] The phenolic resin is purchased from the market and is the same as the prior art CN 107445627 B.

[0091] The main function of the coating organic matter is to wrap the aluminum powder to prevent it from oxidation during the ceramic preparation process. Ultimately, it will be sintered and decomposed in a nitrogen atmosphere. Different coating materials have different effects on the performance of ceramics.

[0092] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A ceramic sintering aid, characterized in that: In parts by weight, it comprises 2-4 parts of manganese dioxide and 4-8 parts of modified aluminum powder, wherein the modified aluminum powder comprises aluminum particles, and the surface of the aluminum particles is coated with an epoxy resin layer; the mass ratio of the aluminum particles to the epoxy resin is 2-3:

1.

2. The ceramic sintering aid according to claim 1, characterized in that: The preparation method of the modified aluminum powder comprises the following steps: uniformly dispersing aluminum particles and epoxy resin in a solvent, and obtaining the modified aluminum powder after drying.

3. The ceramic sintering aid according to claim 2, characterized in that: The added mass of the solvent is 4-9 times the mass of the solid; the drying time is 3-5 hours, and the temperature is 50-70° C.; the solvent is anhydrous ethanol or ethyl acetate.

4. The ceramic sintering aid according to any one of claims 1 to 3, characterized in that: The epoxy resin is bisphenol A epoxy resin; the particle size D50 of the modified aluminum powder is 5-10 μm, and the particle size distribution (D90D10) / D50≤3.

0.

5. A honeycomb ceramic heat storage body, characterized in that: The invention comprises the ceramic sintering aid according to any one of claims 1 to 4.

6. The honeycomb ceramic thermal storage body according to claim 5, characterized in that: The honeycomb ceramic heat storage body comprises, by mass, 6-12 parts of ceramic sintering aid, 40-60 parts of bauxite powder, 2-7 parts of cordierite powder, 1-4 parts of Suzhou kaolin, 0.5-1.5 parts of pyrope powder, 20-35 parts of mullite powder, 2-5 parts of potassium feldspar, 3-9 parts of raw talc; 0.2-0.5 parts of dispersant and 0.5-0.2 parts of grinding aid.

7. The honeycomb ceramic thermal storage body according to claim 6, characterized in that: The dispersant is sodium acrylate; The grinding aid is glycerol; the content of aluminum oxide in the bauxite powder is greater than 80%.

8. A method for preparing the honeycomb ceramic thermal storage body according to any one of claims 5 to 7, characterized in that: The following steps are involved: The raw materials except the ceramic sintering aid are mixed and ball-milled to obtain a mixed material; The mixed material, the kneading agent and the ceramic sintering aid are mixed, kneaded, refined, molded and dried to obtain a dry blank; The dry blank is sintered to obtain the honeycomb ceramic heat storage body.

9. The method according to claim 8, characterized in that The kneading agent comprises 1-4 parts of cellulose, 1-3 parts of palm oil and 0.3-1 parts of polyethylene oxide; the viscosity of the cellulose is 80,000-120,000; the melting point of the palm oil is 24-28°; and the molecular weight of the polyethylene oxide is 1-8 million.

10. The method according to claim 8, characterized in that The sintering process is as follows: in a nitrogen atmosphere, the temperature is raised to 850-950°C at a rate of 5-10°C / min, and then the temperature is raised to 1200-1300°C at a rate of 2-4°C / min, and the temperature is kept for 2-3 hours; then the temperature is lowered, and the nitrogen atmosphere is maintained during the cooling process. When the temperature drops below 300°C, the nitrogen is stopped, and the temperature is continued to cool to room temperature.

Citation Information

Patent Citations

  • Preparation method of phenolic-resin and manganese-dioxide double-layer laminated ceramic powder

    CN107445627A

  • Pyrogenic conductive and low-dielectric constant circuit board

    JP1991030392A

Cited By

  • Forming processing technology of acid-resistant ceramic product

    CN121292952A